Children with isolated growth hormone deficiency: Empty sella versus normal sella - Ismail, Nagwa Abdallah (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Empty sella (ES) may be associated with variable clinical conditions ranging from the occasional discovery of a clinically asymptomatic pouch within the sella turcica to severe intracranial hypertension and rhinorrhea. The need for replacement hormone therapy in ES, as in other syndromes that may cause hypopituitarism, must be assessed for every single hormone, including growth hormone (GH). AIM: To determine whether or not the presence of ES could allow some changes in the GH responses of the isolated growth hormone deficiency (GHD) patients. MATERIALS AND METHODS: We included a cohort of 59 short stature children and adolescents with isolated GHD. According to computed tomography finding, they were classified into 2 groups: Group 1 included 40 children with normal sella and 19 children with ES in Group 2. All patients received recombinant human growth hormone (rhGH) with a standard dose of 20 IU/m(2)/week. RESULTS: The baseline results were not significantly different for all variables except weight standard deviation was smaller with statistical significant difference (P = 0.02). We identified no significant differences when comparing both groups, except for height standard deviation (HTSD) after the first year of therapy which revealed significant difference in favor of group 1. When comparing pre- and the two post-treatments HTSD results of the studied cases, all showed significant changes after GH therapy. The results of related variables pre-and post-treatment in both the groups showed significant improvement in all variables of the two groups of the study. CONCLUSION: Our study showed a similar stature outcome in the two treatment groups.